Hubungan antara Pemberdayaan Psikologis dengan Organizational Citizenship Behavior pada Karyawan PT. Menara Mas Mega Mandiri - Vanissa Vanissa; Nathalia Yesica; Tito Salim; Rianda Elvinawanty; Mukhaira El Akmal; Khairuddin Khairuddin (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
This study was carried out to investigate the relationship between Psychological Empowerment and Organizational Citizenship Behavior. The sample used in this inquiry was employees of PT. Menara Mas Mega Mandiri. The sample determined were 105 employees using a purposive sampling technique. In the context of our research, the Psychological Empowerment scale consists of 33 items, while the Organizational Citizenship Behavior scale comprises 30 items. The Pearson Product Moment is the correlation method used to examine data. From the research findings, It is evident that Psychological Empowerment exerts a beneficial impact. There is a substantial association with Organizational Citizenship Behavior, as indicated by a statistical measure correlation of 0.560 with a significance level of 0.000. This implies that as the level of Psychological Empowerment increases, the level of Organizational Citizenship Behavior among employees also increases, and vice versa.